Resection of Mucosal and Submucosal Gastrointestinal Lesions and a Double Endoscope Experience - Çolak, Şükrü (JSLS, 2019)
AIM: The patients who underwent endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) for mucosal and submucosal lesions of the esophagus, stomach, and duodenum and the advantages of the double endoscope method we used for traction during ESD were evaluated. MATERIAL AND METHODS: The patients who underwent ESD and EMR due to upper gastrointestinal lesions were evaluated retrospectively between January 2014 and April 2018 in our endoscopy unit. RESULT: The mean age of 10 patients with esophageal lesions was 53 years. ESD was performed for 7 lesions and EMR for 3 lesions. The most common lesion was leiomyoma and the median size of the lesions was 1.4 cm (range, 0.6–2.5 cm). The median age of 26 patients with gastric lesions was 61 years. EMR were performed for 11 lesions and ESD for 15 lesions. Double endoscope was used in 6 patients. One patient had intramucosal carcinoma, while the other lesions were benign and dysplasia was the most common lesion. The median size of lesions was 1.8 cm (range, 1–3 cm). All lesions were evaluated with endoscopic ultrasonography. Bleeding was seen in 4 patients and perforation in 1 patient during ESD and defect was closed with endoscopic clips. CONCLUSION: The advantages of endoscopic resections; short hospitalization, low complication rates, patient comfort, and doesn't require the general anesthesia. For endoscopic resection, we think that the second endoscope shortens the duration of the procedure, reduces the complication rate, and increases the comfort of the endoscopist.